Content and complexity of stakeholders’ mental models of socio-ecological systems - Van den Broek, Karlijn; Luomba, Joseph; van den Broek, Jan; Fischer, Helen (Journal of environmental psychology, 2023)
Stakeholders' interactions with environmental resources are influenced by their mental models of the socio-ecological system of the environmental resource. Individual differences in such mental models are particularly important to identify, as diverse mental models may be associated with different behaviour or policy preferences and affect collaborative conservation efforts. In the present work, we explore stakeholders' mental models of a socio-ecological system and assess content and complexity differences across fishing experience levels, migration status, and regions. We mapped Tanzanian fishers' (N = 185) mental models of the drivers of the Nile perch stock fluctuation at Lake Victoria. The findings show that (1) fishers’ mental models were complex and diverse, (2) mental models focused on the causal influence of destructive fishing activities, (3) mental model complexity, but not content, varied across regions, and (4) fishing experience and migration status were not consistently related to mental model complexity or content. These results have important implications for environmental resource management at Lake Victoria.